The tradition of ministerial responsiblity and its role in the bureaucratic management of crises - Stark, Alastair (2011)
The article explores the relationship between the United Kingdom's doctrine of ministerial responsiblity and bureaucratic efforts to control four contemporary crises. Evidence emerges from a series of interview with experienced crisis managers, which draws attention to the way in which this convention: (1) tacitly conditoned the thinking and behaviour of bureaucratic crisis actors throuh their senstivity to political risk; and (2) was reinterpreted and utilized insturmentally by political and bureaucratic agents in response to the dilemmas posed by each crisis. The analysis of these themes connects governance and crisis literatures together by shedding light on the interaction between governance 'traditons', century crisis episodes and the requirements of crisis management. - Reproduced.
Keywords: Ministerial responsibility; Civil service